Towards nanomedicines for neuro-AIDS - Sagar, Vidya (Rev Med Virol, 2014)
Although Highly Active Antiretroviral Therapy (HAART) has resulted in remarkable decline in the morbidity and mortality in AIDS Patients, controlling HIV infections still remain a global health priority. HIV access to the central nervous system (CNS) serves as the natural viral preserve because most anti-retro viral (ARV) drugs possess inadequate or zero delivery across the brain barriers. Thus, development of target-specific, effective, safe and controllable drug-delivery approach is an important health priority for global elimination of AIDS progression. Emergence of nanotechnology in medicine has shown exciting prospect for development of novel drug delivery systems to administer the desired therapeutic levels of ARV drugs in the CNS. Neuron-resuscitating and/or anti-dependence agents may also be delivered in the brain though nanocarriers to countercheck the rate of neuronal degradation during HIV infection. Several nanovehicles such as liposomes, dendrimers, polymeric nanoparticles, micelles, solid lipid nanoparticles, etc. have been intensively explored. Recently, magnetic nanoparticles and monocytes/macrophages have also been used as carrier to improve the delivery of nanoformulated ARV drugs across the blood-brain barrier (BBB). Nevertheless, more rigorous research-homework has to be elucidated to sort out the shortcomings that affect the target specificity, delivery, release and/or bioavailability of desired amount of drugs for treatment of neuroAIDS.